The implementation of discussion method to improve Learning outcomes andstudents’ ipsachivement on Fifth grade student at sd negeri 15 lansano in the District sutera pesisir selatan regency - Amyarnis Amyarnis (Fakultas Sastra Universitas Ekasakti, 2017)
ass Action Research Lansano 15 V Elementary School District of Sutera at the beginning of January’ to March 201 7. Results of study Social Sciences class V SD Negeri 15 Lansano District of Sutera of several replications are still very low. Of the two repetitions the average grade is still below the KKM is 75. The highest score of 70 while the lowest value 50. On the second daily test of 80 and the lowest score 50. The average of the two daily test is 67. The purpose of this study is to improve learning outcomes IPS with the basic competencies' to describe the struggle of the hero on the Dutch and Japanese invaders